Assessment of the economic, social and cultural effects of the development of creative industries in the Republic of Bashkortostan. ("Journal "U". Economy. Management. Finance.", 2026)
The article discusses the economic, social and cultural indicators of creative industries in the Republic of Bashkortostan. The main barriers, risks and limitations of this industry are considered, the main directions of development are formulated.
Keywords: creative industries; economy; culture; risks